Quantum gravitational states of ultracold neutrons as a tool for probing of beyond-Riemann gravity - A.N. Ivanov; M. Wellenzohn; H. Abele (Physics Letters B, 2021)
We analyze a possibility to probe beyond-Riemann gravity (BRG) contributions, introduced by Kostelecký and Li (see Kostelecký and Li (2021) [6]) on the basis of the Effective Field Theory (EFT) by Kostelecký (2004) [4]. We carry out such an analysis by calculating the BRG contributions to the transition frequencies of the quantum gravitational states of ultracold neutrons (UCNs). These states are being used for a test of interactions beyond the Standard Model (SM) and General Relativity (GR) in the qBOUNCE experiments. We improve by order of magnitude some constraints obtained by Kostelecký and Li (2021) [6].